Honor redeemed [large type] - Johnson, Christine (Christine Elizabeth) (Johnson, Christine (Christine Elizabeth). Keys of promise, 2016)
"After the untimely death of her parents, a nearly penniless Prosperity Jones travels to Key West to join her fiancé--only to discover he has married someone else"--